EXPLORING TABOO LANGUAGE IN THE CIVIL WAR MOVIE BASED ON TIMOTHY JAY’S THEORY - Sihite, Dewi Fortuna (Prologue: Journal on Language and Literature, 2026)
This study analyzes the use of taboo language in the movie Civil War (2024) based on Timothy Jay’s theory. The purpose of this research is to identify the types of taboo language used by the characters in the film and to analyze how these expressions reflect emotional reactions and social interactions. This study applies a descriptive qualitative research design. The data were collected from the dialogues spoken by the characters in the movie Civil War (2024). The researcher identified utterances containing taboo expressions and classified them according to Timothy Jay’s categories, including cursing, profanity, blasphemy, obscenity, vulgarity, epithets, and scatology. The results of the analysis show that several types of taboo language are used in the film, particularly epithets, vulgarity, and scatology, which frequently appear in situations of conflict and emotional tension. These expressions are used by the characters to express strong emotions such as anger, frustration, fear, and surprise. The findings also indicate that taboo language in the film functions not only as offensive speech but also as a means of emphasizing emotions and illustrating the intense atmosphere of war and social conflict. Therefore, the use of taboo language in the movie reflects the psychological of the film narrative.